PENERAPAN MULTI-OBJECTIVE OPTIMIZATION ON THE BASIS OF RATIO ANALYSIS (MOORA) METHODÂ DALAM MENGEVALUASI KINERJA GURU HONORER - Sofiansyah Fadli; Khairul Imtihan (Jurnal Informatika dan Rekayasa Elektronik, 2019)
The role of the teacher is very important in the learning process, also advancing the world of education. Because the quality of the teacher becomes a very important aspect, teachers must have competencies that comply with national education standards in order to perform their duties and roles with competency standards that can lead learners to Human beings with knowledge and ability. According to the guidebook for the selection of high achieving teachers, the selection of high achieving teachers to increase the motivation of teachers to improve their professionalism. The selection of outstanding teachers starts from the education unit, Regency/City, province to National. On the basis of why. The government appreciates outstanding teachers as outlined in RI Law No. 14 of 2005 concerning Teachers and Lecturers article 36 paragraph (1) which says that "Teachers who excel, are exceptionally dedicated, and can help in special areas receive awards". One form of appreciation given to outstanding teachers is to help in the promotion of position. The first step is to look for supporting data as mandated by the National Education Minister's Regulation No. 16 of 2007 on the academic qualification standard and the teacher competency standard, then the requirements used in Competency assessment of this teacher in accordance with pedagogic competence, competence, social, and professional competence and each criterion has a sub criteria. The data obtained were further analyzed using the Multi-Objective Optimization Ratio Analysis (MOORA) method used to determine the highest score or the highest teacher award value based on what was determined by the ranking process. With the final goal this method can be used as a solution to problems in improving the performance of honorary teachers.